Effects of Age on Na+,K+-ATPase Expression in Human and Rodent Skeletal Muscle - Wyckelsma, Victoria L.; McKenna, Michael J. (Frontiers in Physiology, 2016)
The maintenance of transmembrane Na+ and K+ concentration gradients and membrane potential is vital for the production of force in skeletal muscle. In ageing an inability to maintain ion regulation and membrane potential would have adverse consequences on the capacity for performing repeated muscle contractions, which are critical for everyday activities and functional independence. This short review focusses on the effects of ageing on one major and vital component affecting muscle Na+ and K+ concentrations and membrane potential and excitability in skeletal muscle, the Na+,K+-ATPase (Na+,K+-pump, NKA) protein.. The review focuses on chronic regulation of the NKA with age in both human and rodent models and highlights a distant lack of research in NKA with ageing and. In rodents, the muscle NKA measured by [3H]ouabain binding site content, declines with advanced age from peak values in early life. In human skeletal muscle, however, there appears to be no age effect on [3H]ouabain binding site content in physically active older adults between 55-76 years compared to those aged between 18-30 years of age. Analysis of the NKA isoforms reveal differential changes with age in fibre-types in both rat and humans. The data show considerable disparities, suggesting different regulation of NKA isoforms between rodents and humans. Finally we review the importance of physical activity on NKA content in older humans. Findings suggest that physical activity levels of an individual may have a greater effect on regulating the NKA content in skeletal muscle rather than ageing per se, at least up until 80 years of age.